Estimation of mediators in the associations between campus green spaces and students’ anxiety: a case study in Nanjing - Diao, Wanting; Li, Silei; Zhao, Bing; Zhang, Fan (Frontiers in Psychology, 2024)
Although a number of scholars have examined the theoretical pathways between green space (GS) and mental health, few have focused on how campus greenness affects the mental health of Chinese youth. Herein, two objective indicators, campus and individual 300-m normalized vegetation index (NDVI) data, were used as independent variables. A questionnaire was used to collect the self-rated anxiety level of students on campuses in Nanjing. Then, we chose “subjective perception of campus GS”, “physical activity”, “social cohesion”, “nature relatedness” and “usage pattern” as mediating variables to explore the pathways between the campus greenery and college student’ anxiety level through correlation analysis, linear regression, and mediation effect test. Results showed the campus-wide NDVI and individual students' 300-m range NDVI had significant negative correlations with anxiety (p = 0.045, p = 0.023). Campus perception, nature relatedness and the frequency of using GS are the pathways through which campus GSs influence student anxiety. Our findings emphasised the importance of subjective perceptions of greenspaces, which provided a direction that can be deepened in future research.